2021
DOI: 10.1016/j.ajog.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem microfocus computed tomography for noninvasive autopsies: experience in >250 human fetuses

Abstract: BACKGROUND: Noninvasive imaging autopsy alternatives for fetuses weighing <500 grams are limited. Microfocus computed tomography has been reported as a viable option in small case series with the potential to avoid an invasive autopsy. Implementation of postmortem microfocus computed tomography in a large cohort as part of routine clinical service has yet been unreported, and realistic "autopsy prevention rates" are unknown. OBJECTIVE: This study aimed to describe the range of abnormalities detectable on fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Previous work has already discussed the benefits of this technique for other uses, such as for imaging excised whole organs [e.g., cardiac ( 19 ), brain ( 20 )] as well as assessing cartilage rings in a pediatric case of tracheal stenosis ( 13 ). Micro-CT is becoming a more widely accepted tool for non-invasive post-mortem whole body fetal imaging ( 10 , 12 ), as it allows internal visualization without surgical dissection. These studies have also demonstrated that iodine based micro-CT does not affect the histologic or immunohistochemical phenotype of normal tissues [skin biopsies and blood vessels ( 21 ) or diseased tissues, including cardiomyopathic cardiac tissue ( 22 ), cystic kidneys ( 23 ), and in neoplastic lesions of the heart ( 24 ), and brain ( 20 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has already discussed the benefits of this technique for other uses, such as for imaging excised whole organs [e.g., cardiac ( 19 ), brain ( 20 )] as well as assessing cartilage rings in a pediatric case of tracheal stenosis ( 13 ). Micro-CT is becoming a more widely accepted tool for non-invasive post-mortem whole body fetal imaging ( 10 , 12 ), as it allows internal visualization without surgical dissection. These studies have also demonstrated that iodine based micro-CT does not affect the histologic or immunohistochemical phenotype of normal tissues [skin biopsies and blood vessels ( 21 ) or diseased tissues, including cardiomyopathic cardiac tissue ( 22 ), cystic kidneys ( 23 ), and in neoplastic lesions of the heart ( 24 ), and brain ( 20 )].…”
Section: Discussionmentioning
confidence: 99%
“…It uses multiple X-rays to create a highresolution 3D volume imaging dataset at a spatial resolution comparable to light microscopy (voxel size down to 1 micron) (9). At our institution, we currently provide a post-mortem fetal micro-CT clinical imaging service (10)(11)(12), however only a few publications have reported using this technology for excised human surgical specimens (13)(14)(15)(16) and the utility of this imaging modality for pediatric thyroglossal duct cyst specimens is unknown, but clearly has appeal in providing high resolution 3D imaging of complex neck structures to aid pathological dissection.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the largest case series published comparing foetal micro-CT with standard autopsy [ 15 , 29 ], both demonstrated high sensitivity and specificity rates for overall diagnosis (94–100% sensitivity, 90–100% specificity) [ 15 , 29 ]. The main drawback, however, was the requirement for tissue staining with an iodinated contrast medium which caused some residual discolouration of the foetus and tissue shrinkage [ 30 ] and can take several days for full iodination to occur, depending on the size of the foetus.…”
Section: How Accurate Are the Different Post-mortem Imaging Modalities?mentioning
confidence: 99%
“…Currently, there are different non-invasive alternatives to an autopsy that allow the study of the human fetal heart. Contrast-enhanced micro-computed tomography (micro-CT) is one of the alternative methods that has proven to be feasible in the postmortem evaluation of the human fetal heart since the 8° WG, reaching adequate detection rate compared to the gold standard technique [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Besides the clinical domain, it can be used for educational and teaching purposes, having the potential to generate overriding medical and non-medical areas for future scientific and engineering advancements in the field of pediatric cardiology [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to other non-invasive postmortem techniques, micro-CT seems to have a better balance between advantages and limitations for studying isolated fetal hearts [ 41 , 42 , 43 , 44 ]. Previously published studies on this technique are heterogeneous in their objectives, studied population, methods and imaging analysis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%